Latín Tradition in a Chilean colonial novel (Iter, 2022)
The first Chilean novel can be foundin the body ofan unpublished Chilean chronicle from the XVIIth century.It is a Baroque narrative which tells about a love relationship betweentwo Mapuche youngsters. In this novel, the author often stops hisnarrative to make roomfor a number of quotations from Latín authors,mainly Ovid and Virgil. Curiously enough, however, these quotationsaren’t but recompositions or “pasticci” of verses which are originallyseparated in the literary work they come from. This quotations,neverthelessy regularly make coherent and clearly meaningful texis. Thispaper attempts to analyze and explain this particular way ofwriting.